2018
DOI: 10.1080/17290376.2018.1527244
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a community-based ART programme after tapering home visits in rural Sierra Leone: a 24-month retrospective study

Abstract: Evaluations of community-based antiretroviral therapy (ART) programmes have demonstrated positive outcomes, but little is known about the impact of tapering community-based ART. The objective of this study was to assess 24-month HIV retention outcomes of a community-based ART programme and its tapered visit frequency in Koidu City, Sierra Leone. This retrospective, quasi-experimental study compared outcomes of 52 HIV-infected persons initiated on community-based ART against 91 HIV-infected persons receiving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…They could then become agents of change in the relationship between professionals at the HC and in the community. 27 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They could then become agents of change in the relationship between professionals at the HC and in the community. 27 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…They could then become agents of change in the relationship between professionals at the HC and in the community. 27,28,29 Bio-psychosocial care approach facilitators as grassroots initiative: What are possible solutions to a difficult change?…”
Section: Challenge Of Barriers To Change the Approach Of Care At The Health Centre Levelmentioning
confidence: 99%
“…In other countries, for example, weakness in drug supply chains have challenged the success of HIV care outside of district hospitals [26]. Availability of and support for trained community health workers or patient peers to enable the success of models for delivering ART in communities has also proven a challenge in other countries and needs to be carefully provided for and monitored in Namibia [28].…”
Section: Plos Onementioning
confidence: 99%
“…Two systematic reviews of peer interventions for HIV have shown an effect on behavioral outcomes but mixed results on clinical outcomes, noting a lack of well-designed comparative studies (16, 17). A study from an Africa country with a similar community based care service model reported high retention among HIV patients on ART compared with the standard of care (73 vs. 44%) (18).…”
Section: Discussionmentioning
confidence: 99%